2017
DOI: 10.1002/14651858.cd010914.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Task-oriented interventions for children with developmental co-ordination disorder

Abstract: We have very little confidence in the effect estimate: the true effect is likely to be substantially different from the estimate of effect. The conclusions drawn from previous reviews, which unanimously reported beneficial effects of intervention, are inconsistent with our conclusions. This review highlights the need for carefully designed and executed RCTs to investigate the effect of interventions for children with DCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 73 publications
0
39
0
Order By: Relevance
“…The prevalence of interventions designed to take one of two specific theoretical approaches was also notable. These approaches were (a) a "task-orientated" approach focused on improving particular functional motor abilities such as handwriting (Miyahara, Hillier, Pridham, & Nakagawa, 2017); (b) an approach focused on training foundational movement patterns that are proposed as building blocks for more contextually specific motor abilities (Logan et al, 2018). In comparison, far fewer interventions adopted more "processes-orientated" approaches purporting to act on underlying sensorimotor mechanisms (e.g., visuomotor integration) that hope to yield more systemic benefits that generalize to all motor abilities.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of interventions designed to take one of two specific theoretical approaches was also notable. These approaches were (a) a "task-orientated" approach focused on improving particular functional motor abilities such as handwriting (Miyahara, Hillier, Pridham, & Nakagawa, 2017); (b) an approach focused on training foundational movement patterns that are proposed as building blocks for more contextually specific motor abilities (Logan et al, 2018). In comparison, far fewer interventions adopted more "processes-orientated" approaches purporting to act on underlying sensorimotor mechanisms (e.g., visuomotor integration) that hope to yield more systemic benefits that generalize to all motor abilities.…”
Section: Discussionmentioning
confidence: 99%
“…For the reliable and valid assessment of the quality of evidence in reviews, primary intervention studies need to fully address the risk of bias specified by Grades of Recommendation, Assessment, Development and Evaluation (GRADE) (Guyatt et al 2011). As a solution for the subgrouping issue, 740 M. Miyahara et al reviewers may have to rely on the original intervention studiesˈ descriptions for the labels of intervention (Miyahara et al 2014) or wait for a development of a specific intervention protocol. Finally, more meta-reviews are needed to ensure the methodological quality of reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Quality and risk of bias of included articles were variable, limiting the robustness of the conclusions resulting from this review. Previous systematic reviews considering task-specific training 13 and motor-based interventions 10 for children with DCD have reported similar findings in regards to small numbers of studies of heterogeneous quality and intervention type, and likewise found difficulties establishing definite conclusions. Movement-based interventions with emerging efficacy for older children with motor impairment, such as task-specific training 52 or goal-directed interventions based on motorlearning principles, 12 require further investigation to determine whether they are effective for children of preschool age.…”
Section: Discussionmentioning
confidence: 91%
“…Movement-based interventions, in which children actively participate in therapy, may facilitate improvements in motor skills and provide opportunity to learn, practise, and consolidate these skills. 2,10 Previous systematic reviews for children with motor impairment have focused on specific diagnoses, such as cerebral palsy (CP) 11,12 or developmental coordination disorder (DCD), 10,13 or focused on specific populations, such as children born preterm, 14 who are at risk of motor impairment. 15 While some interventions are diagnosis specific, others, including movement-based interventions aiming to improve motor skills, may have capacity to improve outcomes for children with a range of diagnoses.…”
mentioning
confidence: 99%
See 1 more Smart Citation